DEVELOPMENT OF MOIST WOUND HEALING METHOD GOVERNANCE MODEL BASED ON PATRICIA BANNER AND KATHERINE KOLCABA THEORY - Ever Mario Lontaan; Blacius Dedi; Susi Nurhayati; Welong Septian Surya (Universitas Karya Husada Semarang, 2025)
Background: Nursing management is the specific responsibility of the nursing manager to plan, organize, direct, and supervise resources, including personnel, equipment, and funds, to provide effective nursing care to patients, families, and the community. The head of the ward is responsible for managing the health care activities in a particular ward. Patricia Benner identified seven key areas in surgical practice, namely the assisting role, teaching and training functions, monitoring diagnosis and patients, managing change, therapeutic interventions, monitoring the quality of practice, and organizational work competencies. Benner developed this concept to describe the practical knowledge and skills in wetting, including the application of moist wound healing methods. Objective: This study aims to develop a governance model for the moist wound healing method based on Patricia Benner and Katherine Kolcaba's theories to improve the quality of wound care at RSUD Anugerah Tomohon. Method: The research design employed an action research method with a qualitative approach. The study sample consisted of 10 nurses working in the wound care unit. Data were collected through in-depth interviews and direct observation and were analyzed using thematic analysis to identify key themes related to the application of the moist wound healing method. Result: the moist wound healing method enhances the quality of wound care and accelerates the healing process. The implementation of the governance model based on Kolcaba and Benner's theories has a positive impact on wound care outcomes. Conclusion: This study recommends that hospitals adopt this model more widely and provide intensive training to nurses to enhance their wound care skills.